PENGGUNAAN METODE DOUBLE EXPONENTIAL SMOOTHING BROWN UNTUK MERAMALKAN KASUS POSITIF COVID-19 DI PROVINSI PAPUA - Ratu Huriyah Ali; M. Nadjib Bustan; Muhammad Kasim Aidid (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2022)
Forecasting is an activity to predict events that will occur in the future. The data used in this study is data on the addition of positive cases of COVID-19 per day in Papua Province from March 21, 2020 to November 25, 2020. The forecasting method used for data that has an element of trend is the double exponential smoothing brown method. The number of additional positive cases of COVID-19 which tends to increase is assumed to be a trend. In this study, the used is = 0.10 which is obtained based on the smallest SSE, MSE, and MAE values. Forecasting the addition of positive cases of COVID-19 in Papua Province for the next 7 days, namely November 26, 2020 to December 2, 2020, obtained additional positive cases of COVID-19 per day as many as 81, 82, 82, 83, 83, 84, and 84.